Chapter 11 Prinsipper ved test-retest-reliabilitet - Haugen, Tommy (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The study aim was twofold: 1) Review basic principles of test-retest reliability, and 2) investigate the reliability of a test procedure of a one-minute time trial on an ergometer bicycle in relatively well-trained young adults. The subjects (N = 12) completed three "all-out" intervals on the bicycle ergometers where average watt produced was recorded. The results of the experiments showed no significant mean differences across tests, high ICC (.996), low CV, TE, and SEM. The findings suggested that the ergometer test had the ability to produce accurate and stable measurements. It also indicated that measurement biases that affected the results did not seem to occur."